(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Yolde shales, limestone, and sandstone in the Gongola Sub-Basin, Northern Benue Trough, Nigeria, were both studied in the field and laboratory using the gas chromatog- raphy-mass spectrometry to expand our knowledge on their origin, relationship, thermal maturities, and paleo-depositional environment. Results obtained from the field studies suggest that the Yolde Formation was deposited between the marine and continental set- tings. Other properties of the transitional environment observed include bioturbation, high fossil content, cross beddings, and evidence of mud crack. Results from the laboratory anal- ysis obtained show that the studied oils are all related and believed to have been sourced from a common petroleum source rock within the studied basin. The total ion current of the oils studied shows the presence of an unresolved complex mixture consistent with oils that have undergone biodegradation. This is because all the studied oils were extracted from outcrop samples. Trisnorhopanes thermal indicators of the studied oils are observed to fluctuate between 1.08 to 1.7 consistent with oil formed from petroleum source rocks that are in the oil window. Equivalent vitrinite reflectance for the studied samples varies roughly from 0.88 to 1 which infers oils generated from rocks within the oil window. This is consistent with the cross plot of sterane ratio C29 20S/ (20S + 20R) versus C32 homohopane ratio (22S/22S + 22R), which also confirms that the studied oils are thermally matured and very close to the peak of oil generation. Cross-plot of n-alkanes/ isoprenoids shows the dominance of organic matter that originated from marine and then mixed environments. The Yolde Formation is known to have a maximum burial depth beyond 2,000 m in some parts of the Northern Benue Trough. This is therefore expected to find non-degraded oils associated with the deeply buried Yolde Formation.